Video-based smartphone app ('VIDEA bewegt') for physical activity support in German adults: a study protocol for a single-armed observational study. Issue 3 (31st March 2020) - Fischer, Tillmann; Stumpf, Paul; Reinhardt, Gesine; Schwarz, Peter E H; Timpel, Patrick
Abstract : Introduction: Insufficient physical activity is one of the most important risk factors for non-communicable diseases. Physical activity should therefore be intensively promoted in all age groups. Several trials suggest that it can be effectively increased through smartphone interventions. However, few of the smartphone-interventions available on the market have been scientifically evaluated. Therefore, the described study aims to assess the short-term and long-term effects of the smartphone intervention 'VIDEA bewegt' to increase physical activity. The trial is designed as a single-armed observational trial to assess effects under real-life conditions. Methods and analysis: The intervention consists of the smartphone-application 'VIDEA bewegt', which is a video-based preventative programme to improve physical activity in everyday life. The application contains several features and components including educational videos, documentation of activity and motivational exercises. A sample size of at least 106 participants is aimed for. The primary objective of this study is to determine the effect of the application on physical activity in German adults. Secondary objectives are to evaluate the self-efficacy, health-related quality of life and usability of 'VIDEA bewegt'. Data collection is based on online questionnaires, as well as system-internal recorded data. Changes of outcomes from baseline to programme completion and follow-up will be calculated. Ethics and dissemination: The Ethics Committee of the Technical University Dresden approved the study on 25 May 2019 (EK 272062019). All data are processed anonymously and stored on servers only accessible by authorised personnel. The results of the study and the results of the usability test are aimed to be published in a scientific journal. Trial registration number: German Clinical Trials Registry (DRKS00017392).